2018
DOI: 10.1145/3238302
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Adjustment of Eyeball Rotation and Pupil Size Jitter for Virtual Characters

Abstract: Eye motions constitute an important part of our daily face-to-face interactions. Even subtle details in the eyes’ motions give us clues about a person’s thoughts and emotions. Believable and natural animation of the eyes is therefore crucial when creating appealing virtual characters. In this article, we investigate the perceived naturalness of detailed eye motions, more specifically of jitter of the eyeball rotation and pupil diameter on three virtual characters with differing levels of realism. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Avatar creation : We adopted the highly realistic human avatar from Jörg et al 12 The avatar's eyeball movement was driven by a point in a 2‐D plane through a point constraint to mimic someone watching a screen. We adjusted the plane's size and distance from the character to match the real world eye tracking setup.…”
Section: Experimental Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Avatar creation : We adopted the highly realistic human avatar from Jörg et al 12 The avatar's eyeball movement was driven by a point in a 2‐D plane through a point constraint to mimic someone watching a screen. We adjusted the plane's size and distance from the character to match the real world eye tracking setup.…”
Section: Experimental Frameworkmentioning
confidence: 99%
“…We added an offset to the noise to make the mean pupil diameter the same as condition scary. We scaled the noise to result in an average amplitude of 0.0023, a value used in Jörg et al 12 They generated procedural pupil jitter for two motions: a reading motion and a motion inspired by an eye tracking calibration procedure where viewers looked nine points on a white board without any changes in light. We used the average noise amplitude for the nine point motion as that type of motion is most similar to our stimuli.…”
Section: Study 3: Pupil Diameter Variation As a Cuementioning
confidence: 99%
See 1 more Smart Citation
“…Your task is to respond to several prompts about the animation after each trial.". Based on prior work we evaluate each interaction in terms of truthfulness [77], naturalness [43], attentiveness [25], comfort with the avatar [32], and eye contact [58]. After watching each animation the participant used a mouse to respond to the following prompts, using a five point Likert scale from 'Strongly Disagree' to 'Strongly Agree'(1-5):…”
Section: Study 2: Avatar Attributesmentioning
confidence: 99%
“…Results from Duchowski et al [23] suggest that data-driven eye animations are perceived as more natural than procedural animations. Jörg et al [43] found that subtle variations in the amplitude of noise within data-driven eye animations influenced how natural the animations were perceived. This suggests that a small amount of spatial noise in the signal may be detected, and have a negative impact on the naturalness of eye animations.…”
Section: Introductionmentioning
confidence: 99%